Product Innovation by Incumbent Firms in Developing Economies : The Roles of Research and Development Expenditures, Trade Policy, and the Investment Climate - Lederman, Daniel (Washington, DC: World Bank, 2012)
A model of firm innovation illustrates the effects of the threat of imitation and product varieties on a representative firm's decision to invest in research and development to produce new product varieties. The model motivates two empirical questions: (1) Is research and development partially correlated with firms' propensity to introduce new products or product innovation in developing countries? (2) Do trade policies and the national investment climate affect firms' propensity for product innovation? The econometric evidence suggests that the answers are yes and yes, but the investment climate affects product innovation in a manner that is consistent with the presence of market failures and state capture. National trade-policy distortions appear to reduce the probability of product innovation, and the density of exporting firms at the national level also seems to positively affect the propensity to introduce new products by individual firms. The paper discusses some policy implications.